2021
DOI: 10.24191/jmeche.v18i2.14995
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop and Flow Characteristics in a Diffuser with a Dimpled Tube

Abstract: The pressure drops and flow characteristics in a diffuser fitted with a semi-dimpled tube are numerically studied. Air is selected as a working fluid and its physical properties are modelled using pressure and velocity distribution. The study reveals that every semi-dimple acts as a vortex generator. They provide the flow with intensive vortices between the dimpled surface and the diffuser wall. Therefore, they cause an enhancement in the pressure drop inside the diffuser. The performance of the dimples consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…A diffuser is a device used to decrease flow velocity [12,13]. In certain occurrences, the diffuser can improve the performance of a cycle or mechanism, such as in the research of Askari and Wisnoe [14], who found in their study on pressure drop and flow characteristics that the addition of a diffuser with semi-circular protrusions on its inner profile can increase recirculation and eddies in the interior around the dimple. McLaughlin et al [15] found that varying a vaned diffuser with a diverging endwall concept can reduce the high-Pressure Ratio (PR) centrifugal compressors' dimensions without sacrificing performance.…”
Section: Introductionmentioning
confidence: 99%
“…A diffuser is a device used to decrease flow velocity [12,13]. In certain occurrences, the diffuser can improve the performance of a cycle or mechanism, such as in the research of Askari and Wisnoe [14], who found in their study on pressure drop and flow characteristics that the addition of a diffuser with semi-circular protrusions on its inner profile can increase recirculation and eddies in the interior around the dimple. McLaughlin et al [15] found that varying a vaned diffuser with a diverging endwall concept can reduce the high-Pressure Ratio (PR) centrifugal compressors' dimensions without sacrificing performance.…”
Section: Introductionmentioning
confidence: 99%